Peningkatan Kinerja Turbin Angin Savonius Tipe L Dengan Variasi Jarak Overlap - Firman, Muhammad; Rendi, Rendi (Proklamasi 45 University, 2024)
This research aims to improve the performance of the Savonius type L wind turbine by varying the overlap distance on the turbine blades. The L type Savonius turbine with two blades is used as a model, with a turbine height of 800 mm and a rotor diameter of 350 mm. The variations in overlap distance used are 20 mm, 30 mm, and 40 mm. The research was conducted at the Mechanical Engineering Laboratory, Department of Mechanical Engineering, Islamic University of Kalimantan. Research data was obtained through direct testing in the field, by measuring the turbine rotation speed and the resulting load. The research results show that the overlap distance has a significant influence on turbine performance. The power coefficient (CoP), torque coefficient (Cm), and static torque coefficient (CTs) values reach their highest point at an overlap distance of 30 mm. However, when the overlap distance exceeds the optimum point, these values tend to decrease. The optimum point is reached at a turbine rotor angle of 90 degrees.